In the interest of everyone? Support for social movement unionism among union officials in Quebec (Canada) - Lorenzo Frangi; Sinisa Hadziabdic; Anthony C. Masi (Industrial Relations Journal, 2022)
Using a mixed-method research design involving interviews and a survey, we examined how union officials in Quebec perceive social movement unionism (SMU). We show that union officials view SMU as a multifaceted phenomenon with ideal and pragmatic dimensions. They are torn between strong support for the ideals of SMU and a practical reluctance to use members' dues to provide services to non-members. Experience with civil society organisations mitigates this tension, encouraging union officials to defend the interests of everyone not only as an ideal, but also as a strategy that allows unions to protect members and unrepresented workers.
Keywords: 330